Caregivers' perception of dignity in teenagers with autism spectrum disorder. (November 2019) - Mohammadi, Fatemeh; Rakhshan, Mahnaz; Molazem, Zahra; Zareh, Najaf; Gillespie, Mark
Introduction: Maintaining dignity is one of patients is one of the main ethical responsibilities of caregivers. However, in many cases, the dignity of patients, especially autistic teenagers is not maintained. The extent to which dignity needs are met for this group within the Iranian care system is difficult to determine as dignity is an abstract concept, and there are few related research studies reported. Objectives: The objective of this study is to find out caregivers perspectives on dignity in teenagers with autistic spectrum disorder. Research design: This study uses a qualitative research design. The data were collected through individual, semi-structured interviews and field notes developed during the interviews. In order to analyze the data, qualitative conventional content analysis was used. Participants and research context: In all, 16 professional caregivers for autistic teenagers working in public hospitals were recruited based on a targeted sampling method to reach data saturation from February 2016 to July 2017. Findings: The findings of this study were presented in three main themes, "privacy, " "respecting individual identity, " and "comprehensive support, " and 11 categories. Ethical consideration: This study's protocol was approved by the Research Ethics Committee of medical universities located in Southeast of Iran and the required ethical principles were followed throughout. Discussion and conclusion: Based on the findings of this study from the perspective of caregivers, autistic teenagers need to be cared for and educated in a respectful environment where their privacy is maintained, their individual identities are respected, and they receive comprehensive familial, social, and financial support. These conditions would maintain the dignity of such teenagers and would result in appropriate behavioral outcomes. Therefore, it is suggested that a cultural, professional and institutional background in which all components of the autistic teenager's dignity are protected and emphasized be provided.